A universal interface layer based on an amine-functionalized fullerene derivative with dual functionality for efficient solution processed organic and perovskite solar cells - Azimi, Seyed Hamed; Ameri, Tayebeh; Ameri, Tayebeh; Zhang, Hong; Hou, Yi; Ramírez Quiroz, César Omar; Min, Jie; Hu, Mengyao; Zhang, Zhi-Guo; Przybilla, Thomas; Matt, Gebhard; Spiecker, Erdmann; et al. (Advanced Energy Materials, 2015)
The successful application of an effective dipolar interface layer based on an amine functionalized fullerene derivative (DMAPA-C60) is reported for the perovskite and organic photovoltaic devices. The incorporation of DMAPA-C60 facilitates a favorable energy level alignment, and results in enhanced mobility-lifetime (μt) produc
Keywords: energy level alignment; mobility-lifetime products; organic photovoltaic devices; perovskite solar cells

High-performance semitransparent perovskite solar cells with solution-processed silver nanowires as top electrodes - Guo, Fei; Azimi, Seyed Hamed; Hou, Yi; Przybilla, Thomas; Hu, Mengyao; Bronnbauer, Carina; Langner, Stefan; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph (Nanoscale, 2015)
In this work, we report efficient semitransparent perovskite solar cells using solution-processed silver nanowires (AgNWs) as top electrodes. A thin layer of zinc oxide nanoparticles is introduced beneath the AgNWs, which fulfills two essential functionalities: it ensures ohmic contact between the PC60BM and the AgNWs and it serves as a physical foundation that enables the solution-deposition of AgNWs without causing damage to the underlying perovskite. The as-fabricated semitransparent perovskite cells show a high fill factor of 66.8%, V-oc = 0.964 V, J(sc) = 13.18 mA cm(-2), yielding an overall efficiency of 8.49% which corresponds to 80% of the reference devices with reflective opaque electrode